Socioeconomic Determinants of Tertiary Rhinology Care Utilization - David M. Poetker MD, MA; David R. Friedland MD, PhD; Jazzmyne A. Adams MPH; Ling Tong MA; Kristen Osinski MS; Jake Luo PhD (OTO Open, 2021)
Objective The objective of this study was to determine the impact of patient demographics and socioeconomic factors on the utilization of tertiary rhinology care services in an upper Midwestern academic medical center. Study Design Retrospective review of electronic health records. Setting Academic medical center. Methods The electronic health record of our academic center was interrogated for the demographics and diagnosis of chronic rhinosinusitis (CRS) among adult patients seen by fellowship-trained rhinologists from 2000 to 2019. Patient characteristics (age, sex, race, insurance status) and population-level data (median income and education level) were compared with utilization of tertiary rhinology services for CRS. Utilization rates were calculated for each regional zip code and correlated with census data for median income and education. The association between determinants of health and tertiary rhinology utilization was assessed by multivariate regression analyses. Results A total of 8325 patients diagnosed with CRS used tertiary rhinology services. Patients were older (median, 58.9 years) and more likely to be female (57.6%), White (85%), and privately insured (60%) when compared with patients seen across our hospital system ( P < .001). Adjusted analyses showed median income, education level, and White race to be independently correlated with tertiary care utilization. Private insurance alone was not an independent contributing factor to access. Conclusion Utilization of tertiary rhinology services correlated with income, race, and education level. Private insurance was not an independent factor. These results highlight social differences in determinants of access to tertiary otolaryngologic care.